Teaching knowledge and Statistical Education: a study on statistical competences and curriculum guidelines from the perspective of a collaborative group of teachers - Karla Priscila Schreiber; Mauren Porciúncula (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
In this paper, teachers' knowledge regarding statistical competences and curriculum documents, mobilized in the Collaborative Group for the Training of Teachers in Statistical Education (MoSaiCo Edu) is highlighted. Considering the Discourse of the collective subject technique, the audio transcription of seven group meetings was analyzed. As a result, one can describe signs of mobilization of professional teaching knowledge related to the insertion of statistics in documents and textbooks. This was noticeable with regard to learning and skills developed by students, with regard to statistical competences, such as educational goals and with regard to the specificities and importance of context and the conceptual and procedural domain of Statistics. In this way, spaces for collaborative work among teachers provide opportunities for sharing and building teaching practices and understanding, favoring the proposition of categories and the legitimization of a specific basis for professional practice and teaching of Statistics.